2014
DOI: 10.1371/journal.pgen.1004044
|View full text |Cite
|
Sign up to set email alerts
|

A Nonsense Mutation in TMEM95 Encoding a Nondescript Transmembrane Protein Causes Idiopathic Male Subfertility in Cattle

Abstract: Genetic variants underlying reduced male reproductive performance have been identified in humans and model organisms, most of them compromising semen quality. Occasionally, male fertility is severely compromised although semen analysis remains without any apparent pathological findings (i.e., idiopathic subfertility). Artificial insemination (AI) in most cattle populations requires close examination of all ejaculates before insemination. Although anomalous ejaculates are rejected, insemination success varies c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
145
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(153 citation statements)
references
References 71 publications
(82 reference statements)
5
145
0
1
Order By: Relevance
“…Although the novel A47A mutation in the pig TMEM95 gene was a synonymous mutation, it may impart an effect on fitness, splice regulation, and miRNA binding (Parmley et al, 2007). Several computational analyses have also indicated that synonymous mutations impact mRNA stability (Chamary et al, 2005;Quax et al, 2015;Lorenz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the novel A47A mutation in the pig TMEM95 gene was a synonymous mutation, it may impart an effect on fitness, splice regulation, and miRNA binding (Parmley et al, 2007). Several computational analyses have also indicated that synonymous mutations impact mRNA stability (Chamary et al, 2005;Quax et al, 2015;Lorenz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several computational analyses have also indicated that synonymous mutations impact mRNA stability (Chamary et al, 2005;Quax et al, 2015;Lorenz et al, 2011). Synonymous mutations affected protein folding and function (Parmley et al, 2007;Gartner et al, 2013). Therefore, the relationships between the SNP locus (A47A) and testis measurement traits in piglet were carried out.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations